Video Gaming May Increase Children’s’ Brain’s Working Fast - Murtazayeva Xadicha Nuriddinovna; Tangirqulova Karomat Saitovna (Zien Journals, 2022)
In this article we will discuss video gaming how to effect to human brain system. Its pros and cons and main features
Keywords: adolescent brain; behavior; neuroimaging studies; video gaming